(untitled) (International Seven Journal of Health Research, 2024)
Neuroscience helps us to understand one of the most relevant aspects: the understanding of the role played by the brain in our biographical history and how human beings confront the dilemma of existence, therefore, it supports us in understanding the role of designers as professionals of intentional visualization and how to face the paradoxes that come into play in the design processes. A little more than two decades ago, not much was known about the brain because of the lack of resources to study and research it. Medicine, like any other science, is based on observation. Once the person died, what happened to the brain was observed and conclusions were drawn. In many cases neuroscience accepted the lesions found and subsequently observed, but not in all cases. The brain holds a map of the evolution of the species, which is nothing but the result of a journey of millions of years from the condition of the tiniest cell; it is a primary and primitive history that houses our homo sapiens brain. The term neuroscience is relatively recent. Its current use corresponds to the need to integrate the contributions of the various areas of scientific research and clinical sciences in understanding the functioning of the nervous system. Current scholars of the brain know that understanding the brain requires breaking down the barriers of traditional disciplines to mention just a few of the areas that have been created, largely to characterize the methods of study. This tendency is very evident in recent scientific works which deal with the more complex functions of this organ, such as emotions and consciousness, relying on the main concepts coming from the various disciplines (Gross, Rocha-Miranda & Bender, 2001, p. 96). As an object of constant study, our brain approaches an epistemological condition of robust and full neuroplastic complexity, since in it reside: memory, affects, perceptions, feelings, intelligences and consciousness. Everything we pay attention to and that emerges strongly in our learning field is what we understand based on our cognitive processes, and we are able to question what is going on in the brain and, when we do, we modify it.